(untitled) (International Journal of Engineering and Computer Science, 2015)
In digital computing world representing information in visual forms has become very important. Due to improvement in computing and network technologies, in past few years we have seen a considerable rise in the accessibility and transmission of digital images using imaging technologies like digital cameras, scanners. This technology is also used for manipulating digital images and creating different forgery in image which is very difficult to identify. In tampering of digital images involved copying one part of image into other part of image, any types of image manipulation operation is consider as a forgery in image. Simple way to image forgery is manipulated image without leaving any perceptible traces; as a result, the authenticity of images can’t be taken for granted. There are no of operation in which we can change the image contain, like scaling, rotating, cropping. Preserving image authenticity is very complex because easily availability and free downloading image editing software. So detecting image forgery is difficult and challenging task. A lot of research has been going on this area and one of the problems is unavability of original image for evaluation. In this paper we studied active and passive or blind approaches to detect forgery in digital image.